Teaching Methods and The Field of Educational Sciences Pose Significant Challenges - Kavilova T (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This text examines the comparison between inclusive policies designed to support children with specific needs and those catering to students from immigrant backgrounds. Initially, it aims to demonstrate how the European political discourse on inclusion in these realms is heavily influenced by the frameworks of human capital and social cohesion, primarily targeting marginalized individuals rather than addressing systemic educational structures. Subsequently, it delves into the intricate processes involved in translating these policy recommendations within the French-speaking Uzbek education system. The authors argue that these political orientations, characterized by soft governance, do not fundamentally challenge the existing educational structures, thus struggling to address the mechanisms that perpetuate differentiation within the educational quasi-market. Lastly, the text proposes recommendations for a comprehensive inclusive policy centered on social justice, emphasizing the need for coordinated action to address cognitive processes of stigmatization and reform school structures.